SOLAR FLARES IN 23rd SOLAR ACTIVITY CYCLE - Chebakova, E. A. (Recent Contributions to Physics, 2011)
Investigation of energy specters of solar cosmic ray (SCR) for 16 flares during 1997-2006 years was carrying out. On the base of neutron monitors (NM) data of world net stations calculation of energy specters were made using geomagnitoshpere as spectrometer.